2015
DOI: 10.3390/v7041726
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Poxvirus Vaccines

Abstract: After Edward Jenner established human vaccination over 200 years ago, attenuated poxviruses became key players to contain the deadliest virus of its own family: Variola virus (VARV), the causative agent of smallpox. Cowpox virus (CPXV) and horsepox virus (HSPV) were extensively used to this end, passaged in cattle and humans until the appearance of vaccinia virus (VACV), which was used in the final campaigns aimed to eradicate the disease, an endeavor that was accomplished by the World Health Organization (WHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
193
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(201 citation statements)
references
References 615 publications
(349 reference statements)
2
193
0
6
Order By: Relevance
“…Therefore, different countries and the WHO have increased their stockpile of smallpox vaccine over the years (4,5). However, the first-generation vaccines used to eradicate smallpox had rates of adverse effects that are not acceptable by current health care standards (6,7).…”
mentioning
confidence: 99%
“…Therefore, different countries and the WHO have increased their stockpile of smallpox vaccine over the years (4,5). However, the first-generation vaccines used to eradicate smallpox had rates of adverse effects that are not acceptable by current health care standards (6,7).…”
mentioning
confidence: 99%
“…Thus, multiple research laboratories are now modifying VACV to develop vectors that retain immunogenicity and have improved safety profiles (73). One strategy used by researchers is to alter the expression of the immune evasion genes of a VACV-based vector (5) in an effort to retain VACV immunogenicity and improve safety. We show here that vΔK1L infection in mouse ear pinnae has decreased pathogenicity but no loss in its ability to activate an acquired immune response or protect against a lethal VACV challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The continued study of VACV remains important because there are reports of VACV infections in animals and humans (2)(3)(4). Moreover, VACV derivatives are now being used as vectors for vaccines against other infectious diseases and as oncolytic virotherapy (5).…”
Section: Abstract K1l Poxvirus Vaccines Vaccinia Virus Viral Pathmentioning
confidence: 99%
“…The most common virus vector to be applied experimentally is the orthopoxvirus vaccinia, successfully used in the vaccination campaign to eradicate smallpox. 35 The observation that a 9000-base-pair segment of the vaccinia virus genome could be deleted without affecting either its infectivity or its ability to replicate led to the development of recombinant vaccinia viruses with inserted foreign genes. Indeed, it has been shown that up to 25,000 base pairs of foreign DNA can be inserted into the virus, which offers the potential for inserting several genes into a single vector to produce a multicomponent vaccine.…”
Section: Virus Vectors: Most Virus Vector Studies Have Concentrated Omentioning
confidence: 99%